Assessing Economic Impacts and Benefits of Commercial Horticulture Extension Programs - Alan Hodges; Shawn Steed; Jane Morse; Peggy Dessaint; Donald Rainey; Charles Vavrina (EDIS)
As fiscal pressures increase from federal and state government agencies to spend public dollars more effectively, it is imperative that the outcomes from educational efforts be clearly documented in terms of measurable changes in knowledge and behavior of clientele or stakeholders. This 5-page fact sheet presents a standardized approach for evaluating the economic impacts of extension educational programs in commercial horticulture in Florida, with which impacts are quantified in terms of measurable changes in revenues, income, or jobs. Written by Alan Hodges, Shawn Steed, Jane Morse, Peggy Dessaint, Donald Rainey, and Charles Vavrina, and published by the UF Department of Food and Resource Economics, September 2011. (AP Photo: Thomas Wright, University of Florida/IFAS)